SUN-166 Primary Adrenal Insufficiency Caused by Underlying Tuberculosis - Jamal, Umara Zahir (J Endocr Soc, 2020)
Introduction Primary adrenal insufficiency (AI) is a rare endocrine disorder affecting 1 in 100,000 people. Primary AI is a gradual destruction of the adrenal cortex. Etiology includes autoimmune, tuberculosis, histoplasmosis, blastomycosis, adrenal metastases, primary adrenal tumors, and opportunistic infections of HIV. Since aggressive treatment of TB, the incidence of TB adrenalitis has significantly declined, now accounting for 20% of reported cases where as autoimmune causes of AI account for 70%. Most common symptoms are non-specific, and diagnosis is often delayed, with patient initially presenting with a life-threatening adrenal crisis. Case Patient is an incarcerated 65 y/o African American male with PMHx of hypothyroidism who was admitted to the hospital for AMS after being found unresponsive in his prison cell. On admission, patient was febrile, hypotensive and tachycardic. He looked disheveled, confused, and lethargic. Other exam findings were negative. Lab results revealed WBC 11.7/μL, serum sodium 116 mmol/L, serum potassium 5.2 mmol/L, serum glucose 68 mg/dL, serum osmolality 237mOsm/kg, TSH 26.3mIU/L, and random cortisol 1.6ug/dL. ACTH stimulation test revealed pre-challenge cortisol levels 5.1ug/dL, 30-minute 4.9ug/dL and 60-minute 4.5ug/dL. ACTH 1271 pg/mL (normal range 7.2-63.3pg/mL). A normal response is a stimulated cortisol level > 18ug/dl. Chest x-ray revealed left lower lobe pneumonia. Clinical signs/symptoms and labs were consistent with primary AI. Adrenal crisis was most likely precipitated by underlying pneumonia. Workup was negative for 21-Hydrolase Antibodies, HIV, CMV, and histoplasmosis. However, QuantiFERON-TB Gold Test was positive. Abdominal CT revealed bilateral enlarged non-enhancing adrenal nodules with coarse calcifications. Biopsy of right adrenal gland revealed necrotizing caseating granulomatous inflammation. Biopsy was negative for isolated aerobic, anerobic, fungal organisms, AFB, and mycobacterium PCR. Due to current findings and high suspicion of TB adrenalitis, patient is currently being treated as culture-negative tuberculosis along with PO hydrocortisone for underlying AI. Discussion Adrenal tuberculosis is a rare cause of primary adrenal insufficiency in developed countries. There should be high suspicion for AI when a patient presents with hypotension, hyponatremia, hyperkalemia and/or hypoglycemia. In this case, although patient did not have a positive AFB culture, he did have a positive QuantiFERON-TB Gold Test along with consistent findings on CT and biopsy. Thus, case was concluded to have high suspicion of primary AI secondary to underlying untreated tuberculosis. Prompt treatment with antituberculosis medication, appropriate steroid therapy, along with monitoring of adrenal function, underlying adrenal insufficiency may be reversible if detected in early stages and decrease mortality.